Low-cell adhesion coating and preparation method thereof

Through the use of free radical copolymerization method and the use of silane coupling agent, the problem of unstable performance of existing low-cell adhesion coatings under different pH conditions was solved, and a low-cell adhesion coating with good hydrophilicity and stability was prepared, which is suitable for a variety of surfaces.

CN119524220APending Publication Date: 2025-02-28INST OF NEW MATERIALS ZHEJIANG UNIV OF TECH PINGHU CITY +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411711742.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing low-cell adhesion coatings have unstable performance under different pH conditions and are prone to fall off, making them difficult to widely used on a variety of surfaces.

Method used

By free radical copolymerization, the hydroxyl group-containing copolymer is bonded to the hydroxylated substrate, and a silane coupling agent is used as a crosslinking agent to achieve multi-point anchoring through the silane and the hydroxyl groups on the side chain of the polymer to enhance adhesion, and form a coating with the properties of inhibiting cell adhesion.

Benefits of technology

The prepared coating exhibits good hydrophilicity and stability, can effectively prevent cell adhesion and maintain excellent inhibitory cell adhesion under different conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524220A_ABST
    Figure CN119524220A_ABST
Patent Text Reader

Abstract

The invention discloses a low-cell adhesion coating and a preparation method thereof, and belongs to the technical field of high polymer materials. The preparation method comprises the following steps: S1, dissolving two hydrophilic monomers and a thermal initiator in ethanol, introducing nitrogen, and heating for reaction; precipitating with diethyl ether after the reaction, drying, and dissolving the obtained polymer in ethanol to form a solution 1; s2, dissolving a silane coupling agent in water, adjusting the pH value, and standing to obtain a solution 2; s3, hydroxylation modification is conducted on the surface of the base material; and S4, mixing the solution 1 and the solution 2, performing ultrasonic treatment, coating a base material with the mixed solution, and drying to obtain the coating. According to the invention, a copolymer with hydroxyl is prepared by adopting a free radical copolymerization method, so that cell adhesion is effectively prevented; the substrate and the copolymer are connected through the silane coupling agent to form a cross-linked network, so that the adhesion and stability of the coating are enhanced. The coating can be widely applied to various hydrophilic or hydrophobic substrates subjected to plasma hydroxylation, and has wide application potential in the biomedical field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and more specifically, to a low cell adhesion coating and a preparation method thereof. Background Art

[0002] After decades of technological development, medical technology has made significant progress. Biomaterials are widely used in medicine, such as medical devices, implants, biosensors, drug delivery, etc. However, the adhesion of cells on the surface of biomaterials may cause a series of problems. For example, abnormal adhesion of cells on the surface of certain medical devices can trigger inflammatory reactions and immune responses, which can cause serious harm to human health; while the adhesion of cells on the surface of specific biosensors will affect their detection sensitivity and accuracy, ultimately leading to detection failure. Therefore, it is particularly important to develop coating materials that can effectively inhibit cell adhesion.

[0003] At present, the common strategy to inhibit cell adhesion is to modify the surface of the substrate. Chalony C et al. formed a zwitterionic polymer coating on the surface of polyurethane (PU) by electrospinning technology to prevent the adhesion of cells and platelets. (Chalony C, Aguilar LE, Park Ch, et al. Drug free anti-cell proliferative and anti-platelet adhesion coating for vascular stents via polymeric electrospun fibers [J]. Materials Letters, 2021, 291: 129545.) However, since there is no chemical reaction between this type of coating and the substrate, it is easy to fall off and it is difficult to maintain its stability. In addition, due to insufficient binding force, the coating is only applicable to certain specific types of substrate surfaces. The patent with publication number CN112691238A discloses a hyaluronic acid coating covalently grafted with phenolamine chemical technology, which can effectively inhibit the adhesion, migration and proliferation of various cells in the blood on the surface of the substrate. Although the adhesion properties of this type of coating show excellent effectiveness under alkaline conditions, its performance will be limited in non-alkaline environments. This phenomenon restricts the wide application of the coating under different pH conditions.

[0004] Therefore, developing a low cell adhesion coating with stable performance, good biocompatibility, and applicability to a variety of surfaces remains an unresolved problem. Summary of the invention

[0005] The object of the present invention is to overcome the deficiencies of the above-mentioned prior art and provide a low cell adhesion coating and a preparation method thereof. The method uses simple free radical copolymerization to bond different hydroxyl copolymers to various hydroxylated substrates, thereby obtaining a coating with cell adhesion inhibition performance. In this method, a silane coupling agent is used as a crosslinking agent between the polymer and the substrate, and multi-point anchoring is achieved through silane and the hydroxyl groups on the polymer side chains to enhance the adhesion. The resulting coating exhibits good hydrophilicity, and a hydration layer is formed on the coating surface through hydration, which effectively prevents cell adhesion.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] A method for preparing a low cell adhesion coating comprises the following steps:

[0008] Step S1, dissolving two hydrophilic monomers and a thermal initiator in ethanol to obtain a prepolymer solution, then introducing nitrogen gas and heating for reaction; after the reaction, precipitating with ether and drying to obtain a polymer, dissolving the polymer in ethanol to form a solution 1;

[0009] Step S2, dissolving the silane coupling agent in water, adjusting the pH value with glacial acetic acid, and allowing to stand to obtain solution 2;

[0010] Step S3, using a plasma cleaning machine to perform hydroxylation modification on the surface of the substrate;

[0011] Step S4, mixing solution 1 and solution 2 to form solution 3, performing ultrasonic treatment, and then coating solution 3 on a substrate, performing drying treatment, to form a low cell adhesion coating.

[0012] The present invention is further configured that the hydrophilic monomers used include but are not limited to: 2-acrylamide, 2-acrylic acid, 2-methacrylic acid, 2-hydroxyethyl methacrylic acid, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, polyethylene glycol monomethyl ether monomethacrylate, N-hydroxyethyl acrylamide, polyvinyl alcohol, N-vinyl pyrrolidone, 4-acryloylmorpholine, 4-vinyl-1,3-dioxolane-2-one, and oligo(ethylene glycol) methyl ether methacrylate; the total mass fraction of the two hydrophilic monomers in the prepolymer solution is 10%-40%.

[0013] The present invention is further configured that in step S1, the initiator used includes but is not limited to: azobisisobutylnitrile, azobisisoheptylnitrile, azobiscyanovaleric acid, dibenzoyl peroxide, potassium persulfate, and ammonium persulfate; the mass fraction of the thermal initiator in the prepolymer solution is in the range of 0.05%-1%.

[0014] The present invention is further configured that in step S2, the silane coupling agent used includes but is not limited to: γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, tetraethyl orthosilicate, γ-chloropropyltrimethoxysilane, vinyltri(β-methoxyethoxy)silane, vinyltrimethoxysilane, and vinyltriethoxysilane.

[0015] The present invention is further configured that, in step S3, the substrate used includes, but is not limited to: polypropylene, silicon, polystyrene, polyvinyl chloride, glass, alumina, polyethylene terephthalate, polytetrafluoroethylene and polyurethane.

[0016] The present invention is further configured such that, in step S1, the heating temperature during the synthesis of the polymer is 50-80°C, and the heating time is 12-48h.

[0017] The present invention is further configured such that, in step S1, nitrogen needs to be introduced for 10-30 minutes before synthesizing the polymer.

[0018] The present invention is further configured such that, in step S2, the pH value is adjusted to 3-5 by using glacial acetic acid.

[0019] The present invention is further configured such that the mass fraction of the polymer in solution 1 is 1-20%; the mass fraction of the silane coupling agent in solution 2 is 1-10%; in step S4, the mixing mass ratio of solution 2 to solution 1 is 1:100-1:10; the coating amount of solution 3 is 0.8×10 -3 ml / cm 2 ; The drying heating temperature range of the coating is 50-120℃.

[0020] A low cell adhesion coating prepared according to the above method.

[0021] In summary, the present invention has the following beneficial effects:

[0022] 1. The coating prepared by the present invention exhibits excellent antifouling performance and has high biocompatibility. By pretreating the surface of the substrate and then coating the prepared copolymer coating, the contact angle of the substrate can be significantly reduced, effectively reducing the attachment of cells to the surface of the substrate.

[0023] 2. In the present invention, the polymer is cross-linked with various hydrophilic and hydrophobic substrate surfaces through a silane coupling agent, and the hydroxyl groups on the silane and polymer side chains are anchored at multiple points, thereby enhancing the binding force between the two and making the coating have excellent stability. After undergoing ultrasound, 3M tape bonding and ultraviolet irradiation, the hydrophilicity of the coating is almost unchanged, and it still maintains good cell adhesion inhibition performance.

[0024] 3. The present invention adopts a simple and easy polymerization method, the raw materials required are low in cost, and ethanol is used as a solvent, which will not cause pollution to the environment. The prepared polymer solution of the low cell adhesion coating can be stored for a long time, which is conducive to production and use. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Schematic diagram of the preparation process of the polymer coating of the present invention.

[0026] Figure 2 Graph showing the water contact angle test results of the polymer coatings prepared in Examples 1 to 3 and Comparative Example 1.

[0027] Figure 3 For Example 1 (HE 1.5 PCH 1 ) and comparative example 1 (PHEMA) polymer coatings as well as the blank control group after culturing L929 cells for 24 hours.

[0028] Figure 4 For Example 1 (HE 1.5 PCH 1 ) and comparative example 1 (PHEMA) polymer coatings as well as the blank control group and bacterial adhesion density statistics after 24 hours of bacterial culture.

[0029] Figure 5 This is a graph showing the water contact angle test results of the coating prepared in Example 1 after ultrasonic treatment for different periods of time. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] The method for preparing the low cell adhesion coating of the present invention comprises the following steps:

[0032] Step S1, dissolving two hydrophilic monomers and a thermal initiator in ethanol to prepare a prepolymer solution (the total mass fraction of the two hydrophilic monomers in the prepolymer solution is 10%-40%, and the mass fraction of the thermal initiator ranges from 0.05%-1%), then introducing nitrogen for 10-30 minutes, and heating the reaction at 50-80° C. for 12-48 hours; after the reaction, precipitating with ether, washing, and drying to obtain a polymer, dissolving the polymer in ethanol to form a solution 1 (the mass fraction of the polymer in the solution 1 is 1-20%).

[0033] In step S1, the hydrophilic monomers used include but are not limited to: 2-acrylamide (AAM), 2-acrylic acid (AA), 2-methacrylic acid (MMA), 2-hydroxyethyl methacrylate (HEMA), 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt (SBMA), polyethylene glycol monomethyl ether monomethacrylate (PEGMA), N-hydroxyethyl acrylamide (HEAA), polyvinyl alcohol (PVA), N-vinyl pyrrolidone (NVP), 4-acryloylmorpholine (AMO), 4-vinyl-1,3-dioxolane-2-one (VDO), oligo(ethylene glycol) methyl ether methacrylate (DMAEMA), preferably polyethylene glycol monomethyl ether monomethacrylate (PEGMA). The initiator used includes, but is not limited to, azobisisobutylnitrile (AIBN), azobisisoheptylnitrile (ABVN), azobiscyanovaleric acid (ACVA), dibenzoyl peroxide (BPO), potassium persulfate (KPS), ammonium persulfate (APS), preferably azobisisobutylnitrile (AIBN).

[0034] Step S2, dissolving the silane coupling agent in water, adjusting the pH value to 3-5 with glacial acetic acid, and standing for 12-48 hours to obtain solution 2 (the mass fraction of the silane coupling agent in solution 2 is 1-10%).

[0035] In step S2, the silane coupling agent used includes but is not limited to: γ-aminopropyltriethoxysilane (KH550), γ-glycidyloxypropyltrimethoxysilane (KH560), γ-methacryloxypropyltrimethoxysilane (KH570), tetraethyl orthosilicate (TEOS), γ-chloropropyltrimethoxysilane (A-143), vinyltri(β-methoxyethoxy)silane (A-172), vinyltrimethoxysilane (A-171), vinyltriethoxysilane (A-151), preferably tetraethyl orthosilicate (TEOS).

[0036] Step S3: using a plasma cleaning machine to perform hydroxylation modification on the surface of the substrate.

[0037] In step S3, the plasma atmosphere used is air, argon, nitrogen or oxygen; the parameters of the plasma cleaning machine are set as follows: power 100W-200W, gas flow 250-350mL / min, treatment time 1-10min. The substrates used include but are not limited to: polypropylene (PP), silicon (Si), polystyrene (PS), polyvinyl chloride (PVC), glass (GLASS), aluminum oxide (Al 2 O 3 ), polyethylene terephthalate (PET), polytetrafluoroethylene (PTFE) and polyurethane (PU), preferably polystyrene (PS) is used.

[0038] Step S4: Solution 2 and Solution 1 are mixed at a mass ratio of 1:100-1:10 to prepare Solution 3, which is then ultrasonically treated and then coated on the substrate (the coating amount of Solution 3 is 0.8×10 -3 ml / cm 2 ), and dried at 50-120°C to form a low cell adhesion coating.

[0039] Figure 1 A schematic diagram of the preparation and application of the coating is shown. First, the substrate is enriched with hydroxyl groups through plasma pretreatment, and then the copolymer coating is prepared through free radical copolymerization. The prepared coating exhibits excellent anti-bacterial adhesion ability.

[0040] The preferred embodiments are as follows:

[0041] Example 1

[0042] 1.3 g 2-hydroxyethyl methacrylic acid (HEMA), 2 g polyethylene glycol monomethyl ether monomethacrylate (PEGMA) and 0.015 g azobisisobutylnitrile (AIBN) were dissolved in 20 ml anhydrous ethanol, nitrogen was introduced for 15 min and then sealed, heated to 65 ° C for 10 h. After the reaction, the product was precipitated with anhydrous ether, washed and dried to obtain the final polymer, and the polymer (0.05 g) was dissolved in anhydrous ethanol (1.5 ml) to obtain solution a. Then, TEOS (1 ml) was dissolved in 30 ml water, and the pH was adjusted to 3 with glacial acetic acid (0.5 ml), and allowed to stand for 24 h to obtain solution b. Solution b and solution a were mixed at a mass ratio of 10:100 to form solution c, which was treated with ultrasound. Then, 100 μl of solution c was taken with a pipette and dropped onto the surface of the pretreated polystyrene substrate (the substrate surface was hydroxylated using a plasma cleaner, and the plasma atmosphere used was argon. The parameters of the plasma cleaner were set as follows: power 100 W, gas flow rate 250 mL / min, and treatment time 10 min). The coating amount of solution c was 0.8×10 -3 ml / cm 2 , and finally placed it in a vacuum oven at 80°C for 24 hours to form a low cell adhesion coating.

[0043] Example 2

[0044] 1.61 g 2-hydroxyethyl methacrylate (HEMA), 1.24 g polyethylene glycol monomethyl ether monomethacrylate (PEGMA) and 0.015 g azobisisobutylnitrile (AIBN) were dissolved in 20 ml anhydrous ethanol, nitrogen was introduced for 15 min, and then sealed, heated to 65 ° C for 10 h. After the reaction, the product was precipitated with anhydrous ether, washed and dried to obtain the final polymer. The polymer (0.05 g) was dissolved in anhydrous ethanol (1.5 ml) to obtain solution a 1 Next, TEOS (1 ml) was dissolved in 30 ml of water, and the pH was adjusted to 3 with glacial acetic acid (0.5 ml). After standing for 24 h, solution b was obtained. 1 . Solution b 1 With solution a 1 Mix them in a mass ratio of 1:10 to form solution c 1 , sonicate, and then use a pipette to draw 100 μl of solution c 1 The solution c was added dropwise to the surface of the pretreated polystyrene substrate (the substrate surface was hydroxylated using a plasma cleaning machine, the plasma atmosphere used was argon, and the parameters of the plasma cleaning machine were set as follows: power 100 W, gas flow 250 mL / min, and treatment time 10 min). 1 The coating amount is 0.8×10 -3 ml / cm 2 , and finally placed it in a vacuum oven at 80°C for 24 hours to form a low cell adhesion coating.

[0045] Example 3

[0046] 1.8 g of 2-hydroxyethyl methacrylic acid (HEMA), 0.83 g of polyethylene glycol monomethyl ether monomethacrylate (PEGMA) and 0.015 g of azobisisobutylnitrile (AIBN) were dissolved in 20 ml of anhydrous ethanol, nitrogen was introduced for 15 min, and then sealed, heated to 65° C. for reaction for 10 h. Subsequently, the product was precipitated with anhydrous ether, washed and dried to obtain the final polymer. The polymer (0.05 g) was dissolved in anhydrous ethanol (1.5 ml) to obtain solution a 2 Next, TEOS (1 ml) was dissolved in 30 ml of water, and the pH was adjusted to 3 with glacial acetic acid (0.5 ml), and allowed to stand for 24 h to obtain solution b. 2 . Solution b 2 With solution a 2 Mix them in a mass ratio of 1:10 to form solution c 2 , sonicate, and then use a pipette to draw 100 μl of solution c 2The solution c was added dropwise to the surface of the pretreated polystyrene substrate (the substrate surface was hydroxylated using a plasma cleaning machine, the plasma atmosphere used was argon, and the parameters of the plasma cleaning machine were set as follows: power 100 W, gas flow 250 mL / min, and treatment time 10 min). 2 The coating amount is 0.8×10 -3 ml / cm 2 , and finally placed it in a vacuum oven at 80°C for 24 hours to form a low cell adhesion coating.

[0047] Comparative Example 1

[0048] 2.15 g 2-hydroxyethyl methacrylic acid (HEMA) and 0.015 g azobisisobutylnitrile (AIBN) were dissolved in 20 ml anhydrous ethanol, nitrogen was passed through for 15 min and then sealed, heated to 65 ° C and reacted for 10 h to obtain a transparent solution, the product was precipitated with anhydrous ether, washed, and dried to obtain a polymer, and the polymer (0.05 g) was dissolved in ethanol (1.5 ml) to obtain solution a 3 Next, TEOS (1 ml) was dissolved in 30 ml of water, and the pH was adjusted to 3 with glacial acetic acid (0.5 ml), and allowed to stand for 24 h to obtain solution b. 3 . Solution b 3 With solution a 3 Mix them in a mass ratio of 1:10 to form solution c 3 , sonicate, and then use a pipette to draw 100 μl of solution c 3 The solution c was added dropwise to the surface of the pretreated polystyrene substrate (the substrate surface was hydroxylated using a plasma cleaning machine, the plasma atmosphere used was argon, and the parameters of the plasma cleaning machine were set as follows: power 100 W, gas flow 250 mL / min, and treatment time 10 min). 3 The coating amount is 0.8×10 -3 ml / cm 2 Finally, it was placed in a vacuum oven at 80°C and dried for 24 hours to form a coating.

[0049] The polymer coatings prepared in Examples 1 to 3 and Comparative Example 1 were tested, and the test results are as follows: Figures 2 to 5 As shown below, combined Figures 2 to 5 To explain:

[0050] Figure 2The water contact angle test results of the polymer coatings prepared in Examples 1 to 3 and Comparative Example 1 are shown in FIG. The results show that based on the fact that PHEMA is rich in hydroxyl groups, the contact angle (WCA) of the polymer coating prepared in Comparative Example 1 is 52°, showing good hydrophilicity; and in Examples 1 to 3, due to the further introduction of PEGMA containing a hydrophilic group -COC-, the hydrophilicity of the coating is significantly improved, and the hydrophilicity of the copolymer coating is further improved as the copolymerization ratio of the hydrophilic monomer increases.

[0051] Figure 3 The fluorescence images of L929 cells in the polymer coatings of Example 1 and Comparative Example 1 and the blank control group after culturing for 24 hours are shown. There is a large amount of cell adhesion in the blank control group, and the cell adhesion in Comparative Example 1 (PHEMA) is reduced compared with the blank control group, while in Example 1 (HE 1.5 PCH 1 , the copolymer of HEMA and PEGMA was named HExPCHy, where x and y represent the molar ratio of the two monomers, respectively), only a few cells adhered to it, indicating that the coating has excellent anti-cell adhesion properties.

[0052] Figure 4 The bacterial adhesion density statistics of the polymer coating of Example 1 and Comparative Example 1 and the blank control group after 24 hours of bacterial culture. The number of the blank control group is 2.8×10 5 cells / cm 2 , Example 1 (HE 1.5 PCH 1 ) is 8×10 4 cells / cm 2 , basically no bacteria adhere, indicating that Example 1 (HE 1.5 PCH 1 )The polymer coating prepared has excellent anti-bacterial adhesion properties.

[0053] Figure 5 The water contact angle test results of the coating prepared in Example 1 after ultrasonic treatment at different times are shown in FIG. The contact angle (WCA) of the coating after 60 minutes of ultrasonic treatment is 26°, and the hydrophilicity of the coating changes only slightly after ultrasonic treatment, indicating that the coating has excellent stability.

[0054] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a low cell adhesion coating, characterized in that: The following steps are involved: Step S1, dissolving two hydrophilic monomers and a thermal initiator in ethanol to obtain a prepolymer solution, then introducing nitrogen gas and heating for reaction; after the reaction, precipitating with ether and drying to obtain a polymer, dissolving the polymer in ethanol to form a solution 1; Step S2, dissolving the silane coupling agent in water, adjusting the pH value with glacial acetic acid, and allowing to stand to obtain solution 2; Step S3, using a plasma cleaning machine to perform hydroxylation modification on the surface of the substrate; Step S4, mixing solution 1 and solution 2 to form solution 3, performing ultrasonic treatment, and then coating solution 3 on a substrate, performing drying treatment, to form a low cell adhesion coating.

2. The method for preparing a low cell adhesion coating according to claim 1, characterized in that: The hydrophilic monomers used include, but are not limited to: 2-acrylamide, 2-acrylic acid, 2-methacrylic acid, 2-hydroxyethyl methacrylic acid, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, polyethylene glycol monomethyl ether monomethacrylate, N-hydroxyethyl acrylamide, polyvinyl alcohol, N-vinyl pyrrolidone, 4-acryloylmorpholine, 4-vinyl-1,3-dioxolane-2-one, and oligo(ethylene glycol) methyl ether methacrylate; the total mass fraction of the two hydrophilic monomers in the prepolymer solution is 10%-40%.

3. The method for preparing a low cell adhesion coating according to claim 1, characterized in that: In step S1, the initiators used include but are not limited to: azobisisobutylnitrile, azobisisoheptylnitrile, azobiscyanovaleric acid, dibenzoyl peroxide, potassium persulfate, and ammonium persulfate; the mass fraction of the thermal initiator in the prepolymer solution is in the range of 0.05%-1%.

4. The method for preparing a low cell adhesion coating according to claim 1, characterized in that: In step S2, the silane coupling agent used includes but is not limited to: γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, tetraethyl orthosilicate, γ-chloropropyltrimethoxysilane, vinyltri(β-methoxyethoxy)silane, vinyltrimethoxysilane, and vinyltriethoxysilane.

5. The method for preparing a low cell adhesion coating according to claim 1, characterized in that: In step S3, the substrate used includes, but is not limited to, polypropylene, silicon, polystyrene, polyvinyl chloride, glass, alumina, polyethylene terephthalate, polytetrafluoroethylene and polyurethane.

6. The method for preparing a low cell adhesion coating according to claim 1, characterized in that: In step S1, the heating temperature during the synthesis of the polymer is 50-80°C, and the heating time is 12-48 hours.

7. The method for preparing a low cell adhesion coating according to claim 1, characterized in that: In step S1, nitrogen gas needs to be introduced for 10-30 minutes before synthesizing the polymer.

8. The method for preparing a low cell adhesion coating according to claim 1, characterized in that: In step S2, the pH value is adjusted to 3-5 by glacial acetic acid.

9. The method for preparing a low cell adhesion coating according to claim 1, characterized in that: The mass fraction of polymer in solution 1 is 1-20%; the mass fraction of silane coupling agent in solution 2 is 1-10%; in step S4, the mixing mass ratio of solution 2 to solution 1 is 1:100-1:10; the coating amount of solution 3 is 0.8×10 -3 ml / cm 2 ; The drying heating temperature range of the coating is 50-120℃.

10. A low cell adhesion coating prepared according to the method of any one of claims 1 to 9.

Citation Information

Patent Citations

  • Material with biological anti-pollution function, and preparation method and application thereof

    CN112691238A